Dispersed settlement in Southern Italy - Dickinson, Robert E. (ERDKUNDE, 1956)
In individual farms (case sparse) live about one fifth of the total and one third of the rural population of southern Italy. The settlement types are: the closed village; smaller centers and hamlets ( casali, frazioni); masserie - old farms of the large estates, usually over 50 ha; podere - more or less independent family farms with varying size depending on the type of economy (under 1 ha for citrus cultivation, up to about 15 ha for wheat fallow cultivation); the hut in the vineyard, olive grove and on the pasture as shelter or for summer use. These settlement units were redrawn from sheets at the scale of 1 : 25 000 and 1 : 50 000 to those at the scale of 1 : 100 000, and the following relationships were recognized (with substantial modification of Biasutti's map) (Fig. 3). Concentration types with low dispersion: 1) large centers and large masseries; 2) large centers, small masseries, some scattered temporary buildings; 3) large centers with medium-sized masseries and small farms. Scattered settlements, often of medieval origin, occur in 4 to 6; 4) throughout the central Apennines, hamlets and isolated farms surround the village centers; it is an area of small farms and some isolated masseria (latifondo contadino); 5) on the coasts and on the mountains of the west of the peninsula, a more intensive farming system has developed supported by micro farms with vineyards, olive trees, fruit, wheat and grasses, often with irrigation and terracing, and has scattered farms and hamlets around the central villages; 6) over 60% of the rural population lives in individual farms, which are closed places with moderately intensive and varied cultivation and livestock - Liri Valley, inner, lower parts of the Apennines (Avellino, Benevento), Crati Valley (Cosenza) and the area of the trulli, NE of Taranto; 7) individual farms of the young colonization and mixed farms of Agro Pontino; 8) Piano Campano with large and overpopulated centers, but with scattered farms on the intensively cultivated areas. (Unpopulated areas have been left white). Figs. 4-7 show 4 typical areas: N. Lucania, the area of the trulli, C. Calabria and Tavoliere. The dispersion dates back in part to before 1800, especially in the case of the masseria. However, there has been a steady expansion of peasant farms since the abandonment of the feudal system in 1806 and since the confiscation of the Church's forest land in the 1860s. The extensively cultivated (wheat fallow) latifundia holdings were partially replaced by peasant and estate holdings with more intensive farming practices (vine, olive tree, fruit, fall-sown grasses with livestock). The peasantry could acquire land by purchase, lease (monetary and sharecropping) or, to a lesser extent, by subdivision of the communal land. As a result of the comphz1erty and insecurity of tenure and the poverty and ignorance of the population, development has been very slow. The ongoing programs seek to accelerate the process by establishing farmer positions on confiscated portions of extensively farmed large estates and intensifying agriculture (vineyards, olive trees, fruit, crash crops, and in particular fall-sown grasses and livestock) through material assistance and technical instruction. The main areas affected are Tavoliere, Fossa Premurgiana, Metaponto, Sila and their Ionian coastal lands.